Zn Dopants Synergistic Oxygen Vacancy Boosts Ultrathin CoO Layer for CO2 Photoreduction. (29th December 2021) - Chen, Kui; Jiang, Tongtong; Liu, Tianhu; Yu, Jing; Zhou, Sheng; Ali, Asad; Wang, Shuhui; Liu, Yu; Zhu, Lixin; Xu, Xiaoliang
Abstract: Photoreduction of CO2 without photosensitizers and scavengers runs into the development bottleneck for lack of excellent photocatalysts and ambiguous reduction mechanism. Herein, an ultrathin CoO layer containing Zn‐dopants and O‐vacancies (Vo ‐Zn‐CoO) is designed as an archetype to explore the influence mechanism of Zn on O‐vacancies in ultrathin nanolayer for CO2 photoreduction. DFT calculations illustrate that Zn‐dopants not only reduce formation barriers of *COOH and *CO intermediates, but also form π‐back‐bonding with *CO stimulating CH4 evolution. Finally, Vo ‐Zn‐CoO layer significantly enhances CO2 photoreduction efficiency and CH4 selectivity with 26.8 µmol g −1 h −1 (63.8%) compared to 7.2 µmol g −1 h −1 (23.6%) for CoO layer with O‐vacancies. Moreover, the synergistic effect of Zn and O‐vacancies benefits the stability of O‐vacancies in photocatalysts, achieving durable photocatalytic performance of Vo ‐Zn‐CoO layer. This work manifests that the strategy of metal atoms synergistic O‐vacancies is effective to optimize CO2 photocatalytic efficiency, selectivity, and stability of photocatalyst with O‐vacancies. Abstract : Ultrathin Vo ‐Zn‐CoO layers containing oxygen vacancy cooperated Zn dopants are designed and synthesized, which reduce reaction barriers, stimulate CH4 evolution, and stabilize oxygen vacancy, realizing high efficiency, durable, and directed CO2 photocatalytic conversion. This work provides reliable theoretical and experimental support for the strategy of metal atoms synergistic O‐vacancies in atomic layer optimize CO2 photocatalytic performance (efficiency, selectivity, and stability).